Inhalant Abuse: A New Psychoactive Trend With Clinical And Forensic Implications - Gonçalo Pinto Anjo (2022)
"Inhalants" is a term used to describe volatile compounds that may be inhaled accidentally or intentionally. The prevalence of inhalant abuse is increasing among people, being more prevalent in adolescent men. Inhalants are readily available, relatively inexpensive, and unrestricted sell-ing, when comparing to conventional drugs. Abusers intentionally inhale volatile solvents, ni-trites, among others (this topic will be explored in greater detail throughout this work), in order to produce euphoria, pleasant experiences and psychomotor effects. The methods like huffing, sniffing, snorting, spraying, chroming, or bagging are frequently used for inhalation abuse. People who tend to abuse inhalants over other substances, justify it by arguing that they produce quicker experiences of pleasurable sensations (also referred as "high"), within seconds, although it only lasts for a few minutes. Another argument in their favor is the fact that they do not have any withdrawal symptoms, and it even helps managing the withdrawal of other substances, as we will see later. Although it is a substantial matter, inhalant abuse has not been studied enough. Therefore, this literature aims to provide an overview of inhalant abuse, inhalation method, asso-ciated toxicity, as well as its treatment possibilities and suggestions for the future scientists who may venture into this topic.